Rancang Bangun Aplikasi Surat Menyurat Tata Usaha Madsrah Tsanawiyah Negeri 4 Sumbawa Berbasis Web - Marliana; Esabella, Shinta (AMIK STIEKOM SUMATERA UTARA, 2025)
The management of correspondence at MTsN 4 Sumbawa was previously carried out manually, leading to several issues such as the risk of lost archives, time-consuming searches, and inefficiencies in report generation. This research aims to design and develop a web-based administrative correspondence application to manage incoming letters, outgoing letters, and reports in a structured, fast, and secure manner. The development method used is Agile Development, which includes the stages of requirement analysis, system design, implementation, and testing. The application was developed using PHP programming language with the Laravel framework, MySQL database, and a user interface built with HTML, CSS, and JavaScript. Key features include incoming and outgoing letter management, data search and filtering, archiving, automatic report generation, and digital signatures with role-based access control (admin, head of administration, principal).